Pengaruh Pengawasan Pimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai Inspektorat Kabupaten Pangandaran - Sugeng Purwosuwoyo; Aini Kusniawati (Master Manajemen, 2023)
This study was conducted because several problems were identified where supervision carried out by the leadership was still not optimal. This is evidenced by the existence of violations committed by both those being supervised and those supervising. In addition, slightly loose supervision does not rule out the possibility of violations of the main duties and functions of inspectorate employees. Employee work motivation still fluctuates in the sense that it is not optimal. This can be seen from the attendance records and completion of work targets that are not in accordance with the time that has been determined. The performance of the Pangandaran Regency Inspectorate seems to be slowing down, many jobs are not completed on time and the targets that have been determined. Of course, it cannot be denied that with few personnel, and the implementation of supervision that must be carried out throughout the district, it certainly has an effect on all jobs that must be completed. The aim is to determine the effect of leadership supervision and work motivation on the performance of inspectorate employees in Pangandaran Regency. The method used in this study is qualitative descriptive research. Based on the results of the research and discussion, the following conclusions were obtained. Supervision of the leadership of the Pangandaran Regency Inspectorate tends to be very high, as well as employee performance which tends to be high. This provides a fairly strong relationship between leadership supervision and employee performance. The calculation results show that leadership supervision has a positive and significant effect on employee performance. The work motivation of Pangandaran Regency Inspectorate employees tends to be very high, as well as employee performance which tends to be high. This provides a fairly strong relationship between employee work motivation and employee performance. The calculation results show that employee work motivation has a positive and significant effect on employee performance.